What’s Your STEMspiration?: Adaptation and Validation of A Survey Instrument - Hargraves, Rosalyn Hobson; Morgan, Kristin L.; Jackson, Holly; Feltault, Kelly; Crenshaw, Jasmine; McDonald, Kevin G.; Martin, Marcus L. (Frontiers in Education, 2021)
Millions of dollars each year are invested in intervention programs to broaden participation and improve bachelor degree graduation rates of students enrolled in science, technology, engineering and mathematics (STEM) disciplines. The Virginia–North Carolina Louis Stokes Alliance for Minority Participation (VA–NC Alliance), a consortium of 11 higher education institutions and one federal laboratory funded by the National Science Foundation (NSF), is one such investment., The VA–NC Alliance partners implement evidence-based STEM intervention programs (SIPs) informed by research and specifically designed to increase student retention and graduation rates in STEM majors. The VA–NC Alliance is conducting an Alliance-wide longitudinal research project based in Social Cognitive Career Theory (SCCT) titled “What’s Your STEMspiration?” The goal of the research project is to assess the differentiated impacts and effectiveness of the Alliance’s broadening participation efforts and identify emergent patterns, adding to the field of knowledge about culturally responsive SIPs. In other words, “What’s Your STEMspiration?” explores what influences and inspires undergraduates to pursue a STEM degree and career; and how does the development of a STEM identity support students in achieving their goals. In order to complete this research, the research team developed a survey instrument to conduct the quantitative portion of the study. Two preliminary studies, statistical analysis and cognitive interviews were used to develop and validate the survey instrument. This paper discusses the theoretical and conceptual frameworks and preliminary studies upon which the survey is built, the methodology used to validate the instrument, and the resulting final survey tool.